Collective Mobilization and the Struggle for Squatter Citizenship: Rereading “Xenophobic” Violence in a South African Settlement - Tamlyn Jane Monson (International Journal of Conflict and Violence, 2016)
Given the association between informal residence and the occurrence of “xenophobic” violence in South Africa, this article examines “xenophobic violence” through a political account of two squatter settlements across the transition to democracy: Jeffsville and Brazzaville on the informal periphery of Atteridgeville, Gauteng. Using the concepts of political identity, living politics and insurgent citizenship, the paper mines past and present to explore identities, collective practices and expertise whose legacy can be traced in contemporary mobilization against foreigners, particularly at times of popular protest. I suggest that the category of the “surplus person”, which originated in the apartheid era, lives on in the unfinished transition of squatter citizens to formal urban inclusion in contemporary South Africa. The political salience of this legacy of superfluity is magnified at times of protest, not only through the claims made on the state, but also through the techniques for protest mobilization, which both activate and manufacture identities based on common suffering and civic labour. In the informal settlements of Jeffsville and Brazzaville, these identities polarised insurgent citizens from non-citizen newcomers, particularly those traders whose business-as-usual practices during times of protest appeared as evidence of their indifference and lack of reciprocity precisely at times when shared suffering and commitment were produced as defining qualities of the squatter community.